Opposite effects of estradiol and progesterone on woman's disgust processing - Liu, Mei; Zhang, Xia; He, Zhengming; Liang, Yuan; Zou, Bihong; Ma, Xianjun; Gu, Simeng; Wang, Fushun (Frontiers in Psychiatry, 2023)
Background Ovarian hormones play a critical role in emotion processing, which may be a major reason for the high rates of major depressive disorders in women. However, the exact roles of estradiol and progesterone in emotional processing remain unclear. To this end, we performed behavioral and rs-fMRI studies on the effects ovarian hormones on disgust emotion. Methods In Experiment 1, 95 Chinese female undergraduates completed the single category implicit association test (SC-IAT) and explicit measures of disgust intensity task, 32 in the menstrual phase, 30 in the follicular phase, and 33 in the luteal phase. In Experiment 2, A total of 25 healthy female undergraduates completed three sessions of the rs-fMRI. The menstrual group was scanned during cycle days 2–5, the follicular group during cycle during days 10–13, and the luteal group was scanned 3–7 days before the next menstruation. Results The behavioral results showed that women during the luteal phase had higher D scores and shorter response times (RTs) to disgust stimuli compared to the menses and follicular phases. In contrast, women during the follicular phase had fewer feelings of disgust and longer RTs to pathogen stimuli compared with that during the menses and luteal phases, but this effect was moderated by the intensity of the stimuli. rs-fMRI studies showed that women during the luteal phase have higher functional connectivity in the salience network than those in the follicular phase. Compared with the menstrual phase, women have lower functional connectivity in the amygdala during the follicular phase. Conclusion In summary, a more negative attitude to disgust stimuli and the enhanced functional connectivity of the salience network during the luteal phase may be associated with high progesterone levels, whereas lower disgust feelings and reduced functional connectivity of the amygdala during the follicular phase may be associated with high estradiol levels.